ANALISIS PENGUKURAN TARIF RAWAT INAP STUDY KOMPARATIF ANTARA FULL COSTING DAN ACTIVITY BASED COSTING PADA RS MEILIA CIBUBUR (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2023)
Â This study aims to analyze and compare the calculation of service costs for patients treated at Meilia Cibubur Hospital using the full costing and ABC methods. The aim of the research is to find out about inpatient unit will be carried out ; How to calculate fixed costs and variable costs in the inpatient unit at Meilia Cibubur Hospital How to calculate the rate for each inpatient in the Meilia Cibubur Hospital inpatient unit based on the Full Costing method and the ABC Method. How to calculate the cost per unit for inpatients using the Full Costing method and the ABC Method in the inpatient unit of Meilia Hospital Cibubur. The research results identified differences in how to calculate the cost of production which describes the calculation of patient hospitalization rates. The ABC method has accurate calculations with the cost diver so that all costs will be charged to the patient evenly. Meanwhile, the Full costing method calculates limited costs to fixed costs and variable costs. There is a difference in costs in calculating tariffs which is the difference between the two methods.Â Keword : Full Costing, Activity Based Costing, Measurement of hospitalization rates.